THE SCHOOL ADMINISTRATION ROLES IN THE IMPLEMENTATION OF COMPUTER BASED TEST – NATIONAL EXAMINATION IN EAST ACEH, ACEH, INDONESIA - AHMAD, MUSHTAQ (Advances in Social Sciences Research Journal, 2019)
The purpose of this study is to find out to what extent school administration in East Aceh administered the CBT-NE are ready for accepting Computer Based National Examination (CBNE) in terms of its objective, infrastructure and human resource management, budget allocated management and management of examination. This study employed a qualitative case study approach consisting of three schools from three distinct categories such as general secondary school, secondary boarding school and vocational school in East Aceh District. All the selective schools have implemented the CBT-NE system for students. For collecting data, the researcher conducted interviews with the selected schools’ principals. The research findings report on the variety of preparation that these three schools had taken in implementing CBNE. In terms of infrastructure and human resource management, they followed the instruction provided by the Ministry of Education, Indonesia, while there is also additional equipment that they prepared as well to maintain the electric supply. Moreover, schools got both financial and non-financial supports from the government that allocated to purchase and repair the computer, and honorarium in CBT-NE in their schools. In terms of management role, the schools conducted training for students and teachers to manage the session and community involvement in conducting CBNE.